«Calami ulla exaratione»: Il libro liturgico a stampa dal 1457 al 1596 - Cortoni, Claudio Ubaldo (Archivo Dominicano, 2024)
The invention of the moveable type printing press meant that liturgical books could be copied and distributed quicker than before. In this article are presented the liturgical books printed throught Europe since the invention of the type mobile printing press until the end of the 16th century, and the work behind the press and his evolution.